2022
DOI: 10.1016/j.rbmo.2021.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Decisional needs of patients considering preimplantation genetic testing: a systematic review

Abstract: This review reports on the needs and sources of support in patients" decision-making regarding the uptake of preimplantation genetic testing. Five databases were searched systematically to capture qualitative and quantitative studies. A total of 2,336 articles were screened by title and abstract. Twelve articles met the eligibility criteria and reported on 4,047 participants. This review shows that patients need information directly relevant to PGT treatment, and information on healthcare relating to treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…At least 1 study has analyzed this, and authors concluded that the member of the couple who would be carrying the pregnancy had a higher influence on the couple's decision-making for whether to pursue PGT-M. 24 A recent systematic review of patients' needs during decision-making for PGT-M noted that too many complex details may be a barrier to decision-making for couples, and decisional support may come from a combination of resources (e.g., mass media, significant persons in their life, and different health professionals including genetic counselors and physicians). 25 With this in mind, clinicians should expect that both partners may have concerns to explore during their decision-making.…”
Section: Decision-making For Couplesmentioning
confidence: 99%
“…At least 1 study has analyzed this, and authors concluded that the member of the couple who would be carrying the pregnancy had a higher influence on the couple's decision-making for whether to pursue PGT-M. 24 A recent systematic review of patients' needs during decision-making for PGT-M noted that too many complex details may be a barrier to decision-making for couples, and decisional support may come from a combination of resources (e.g., mass media, significant persons in their life, and different health professionals including genetic counselors and physicians). 25 With this in mind, clinicians should expect that both partners may have concerns to explore during their decision-making.…”
Section: Decision-making For Couplesmentioning
confidence: 99%
“…It has been demonstrated that selecting euploid or no-gene defect embryos for implantation by PGT could decrease the chance of having a foetus with a chromosomal or genetic disease [ 4 , 5 ]. PGT can be divided into 3 groups according to clinical indications: PGT for aneuploidy (PGT-A), PGT for structural rearrangement (PGT-SR) and PGT for monogenic conditions (PGT-M) [ 6 , 7 ]. The clinical indications for PGT-A include advanced maternal age (≥ 38 years), recurrent abortion and recurrent implantation failure [ 8 ].…”
Section: Introductionmentioning
confidence: 99%